(untitled) (Eurasian Journal of Philology Science and Education, 2019)
The article describes the orthoepic and episodic features of modern scientific discourse. Since discourse is a polysemantic concept in linguistics. Types of discourse: scientific, business, military, poetic, advertising, oratory, children’s, economic, pedagogical, electronic, etc. The Features and diversity of each type of discourse is considered in scientific research. Therefore, it is necessary to comprehensively consider the application of discourse and its features in modern linguistics. The article deals with the orthoepic and intonation features of scientific discourse on the basis of experimental research. There is a need to consider the features of each discourse, the study of experimental research. Especially at this time it is important to study the orthoepy and prosodic of politicians, scientists, well-known public figures, as well as the study of their discourse. The orthoepic norm among young people is not observed. Therefore, the article considers phonetics-prosodic analyses of the material and gives the orthoepic norm of the text. The article also analyzes the scientific fragments of the text of the discourses of scientistsprofessors F. Orazbayeva and M. Malbakov. In the course of the study, the orthoepic norms, prosodic and intanational features of the discourses of scientists were analyzed and on the basis of experimental analyses, the orthoepic, prosodic, intanational models of fragments of texts were proposed. As a result of classroom analyses, intonation marks of the text are inserted and intonation features of each discourse of philologists are analyzed.